2022
DOI: 10.1371/journal.pone.0268920
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with malignant duodenal obstruction after receiving self-expandable metallic stents: A single center experience

Abstract: Objectives Self-expandable metallic stent (SEMS) placement is a safe and effective palliative treatment for malignant gastric outlet obstruction; however, the clinical outcomes of gastric and duodenal stenoses may differ. This study aimed to investigate the clinical efficacy of SEMS placement and the predictors of clinical outcomes, specifically in malignant duodenal obstruction (MDO). Methods Between September 2009 and March 2021, 79 patients with MDO who received SEMS placement in our hospital were retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Patency was similar to the previous reports. 11,12,18 The patency can be exaggerated due to short survival time (median 90 days). However, as median patency is longer than the median survival, secondary stenting would be a good option for obstructed duodenal stent.…”
Section: Discussionmentioning
confidence: 99%
“…Patency was similar to the previous reports. 11,12,18 The patency can be exaggerated due to short survival time (median 90 days). However, as median patency is longer than the median survival, secondary stenting would be a good option for obstructed duodenal stent.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Previous retrospective studies investigating poststent chemotherapy after GDS placement reported improved survival outcomes. 7,[9][10][11][12][13][14][15] However, none of these reports performed a time-dependent analysis, which might have accentuated the impact of chemotherapy on survival due to an immortal time bias. Timedependent exposures, such as post-stent chemotherapy, have been suggested to be included as time-dependent variables in hazardbased analyses to minimize the risk of immortal bias in observational studies of survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In all of these reports, chemotherapy after GDS placement reportedly improved the prognosis of MGOO patients. 7,[9][10][11][12][13][14][15] However, no study has yet analyzed the effect of chemotherapy as a time-dependent covariate on survival after GDS placement. Furthermore, there are no reports on the prognostic impact of clinical disease course following GDS placement, such as stent dysfunction or complications of cholangitis associated with bile duct obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The recent developments in intensive chemotherapy are expected to prolong survival in patients with gastric and pancreatic cancers and associated GOO. Chemotherapy after stent placement is helpful in extending the survival period in all carcinomas ( 40 , 41 , 48 , 49 ), pancreatic cancers ( 50 , 51 ) and non-pancreatic cancers ( 51 ).…”
Section: Considerations For Endoscopic Stentingmentioning
confidence: 99%
“…The results of previous studies regarding the predictors of survival in patients with malignant GOO are shown in Table 6 . Various predictors have been reported ( 40 , 41 , 48 , 49 , 57 59 ). Further studies are warranted to establish suitable predictors of survival time.…”
Section: Considerations For Endoscopic Stentingmentioning
confidence: 99%